Comparative Analysis of Flat Prices in Prague and Warsaw (2005-2025); Supply, Demand and Key Market Determinants - Němeček, Michal (2025)
This is bachelor thesis provides a comparative analysis of flat price development and housing affordability in Prague and Warsaw between 2005 and 2025. The study covers the key housing market variables that have impact on supply and demand, including government interaction, building activity, income growth, mortgage conditions, demographic shifts, and the level of tourism. The theoretical framework is based on classical housing market models, primarily the DiPasquale and Wheaton (1996) model, supported by additional concepts of supply elasticity, regulatory obstacles, urbanization, and the housing affordability ratio (HAR) as an indicator of long-term affordability. The empirical part is provided by secondary statistical data from Eurostat, OECD, CZSO, GUS, Deloitte Property Index and national financial institutions. The focus is to compare apartment prices, income levels and affordability using HAR, with an emphasis on the relationship between price growth and wage developments. The findings show that both capital cities have seen price increases, although Prague poses significantly greater housing affordability problems because housing supply is less responsive to demand. Warsaw, on the other hand, has a higher construction engagement rate and a wider land base for new construction. The research concludes that the main problem of the housing market in Prague is the issue of affordability, with a constant mismatch between demand and supply, which is enforced by regulation. Affordability in Warsaw is not much better than in Prague, but flexibility on the supply side continues to moderate price increases. The result of this thesis is that future policy should focus primarily on simplifying spatial plans, expanding housing construction capacity, and balanced mortgage regulation with the aim of improving mortgage availability in both cities.